An updated study of mortality among North American synthetic rubber industry workers. Issue 12 (18th November 2005) - Sathiakumar, N; Graff, J; Macaluso, M; Maldonado, G; Matthews, R; Delzell, E
Abstract : Aim: This study evaluated the mortality experience of workers from the styrene-butadiene industry. Methods: The authors added seven years of follow up to a previous investigation of mortality among 17 924 men employed in the North American synthetic rubber industry. Analyses used the standardised mortality ratios (SMRs) to compare styrene-butadiene rubber workers' cause specific mortality (1943–98) with those of the United States and the Ontario general populations. Results: Overall, the observed/expected numbers of deaths were 6237/7242 for all causes (SMR = 86, 95% CI 84 to 88) and 1608/1741 for all cancers combined (SMR = 92, 95% CI 88 to 97), 71/61 for leukaemia, 53/53 for non-Hodgkin's lymphoma, and 26/27 for multiple myeloma. The 16% leukaemia increase was concentrated in hourly paid subjects with 20–29 years since hire and 10 or more years of employment in the industry (19/7.4, SMR = 258, 95% CI 156 to 403) and in subjects employed in polymerisation (18/8.8, SMR = 204, 95% CI 121 to 322), maintenance labour (15/7.4, SMR = 326, 95% CI 178 to 456), and laboratory operations (14/4.3, SMR = 326, 95% CI 178–546). Conclusion: The study found that some subgroups of synthetic rubber workers had an excess of mortality from leukaemia that was not limited to a particular form of leukaemia. Uncertainty remains about the specific agent(s) that might be responsible for the observed excesses and about the role of unidentified confounding factors. The study did not find any clear relation between employment in the industry and other forms of lymphohaematopoietic cancer. Some subgroups of subjects had more than expected deaths from colorectal and prostate cancers. These increases did not appear to be related to occupational exposure in the industry.